Fundamentals of geology - Roy, A.B (Alpha Science International, 2010)
Provides descriptions of the physical Earth including its primary constituents: minerals and rocks. This book also deals with two different aspects of the dynamic Earth: study of the past worlds based mainly on rock records; and, the dynamic system that brings about changes in the Earth evolving distinctive large- and small-scale features.